2013
DOI: 10.17265/2161-6221/2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Elastic-Plastic Transition under Uniaxial Stress BCC Tantalum

Abstract: Classical molecular dynamics and lattice dynamics were utilized to study the elastic-plastic transition underuniaxial stress in defect free body center cubic (BCC) Tantalum crystals. We demonstrate that the nucleation of defects at the time scales of molecular dynamics in tantalum is due to dynamical instabilities (soft-phonons). Uniaxial compressions test were simulated along the crystallographic directions (100), (110) and (111). The results show that the nucleation of defeccts in the direction (110) is due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 44 publications
(41 reference statements)
1
7
0
1
Order By: Relevance
“…(100) orientation of tantalum and (ii) the maximum shear (Tresca) stress was found to exceed the theoretical shear strength of tantalum on the (010) orientation but was well within for the (110) and (111) orientations. This unique observation on the (010) plane seems to be in accord with a recent study [6] where the elastic-plastic limit of Ta was observed to go past the theoretically predicted critical shear stress. Figure 6: P-h plots obtained from the MD simulation for the three cases using rigid tantalum indenter where H is material's hardness at micro or nanoscale, h is indentation depth, l 1 ,l 2 and l 3 are the material's length scale for region I, II and III respectively, H 1 , H 2 , H 3 , n 1 , n 2 , n 3 are material constants while δ u and δ 1 are the indentation depths that separate regions, I, II and III respectively.…”
Section: Analysis Of Dislocations and Crystal Defects In The Ta Substsupporting
confidence: 91%
See 2 more Smart Citations
“…(100) orientation of tantalum and (ii) the maximum shear (Tresca) stress was found to exceed the theoretical shear strength of tantalum on the (010) orientation but was well within for the (110) and (111) orientations. This unique observation on the (010) plane seems to be in accord with a recent study [6] where the elastic-plastic limit of Ta was observed to go past the theoretically predicted critical shear stress. Figure 6: P-h plots obtained from the MD simulation for the three cases using rigid tantalum indenter where H is material's hardness at micro or nanoscale, h is indentation depth, l 1 ,l 2 and l 3 are the material's length scale for region I, II and III respectively, H 1 , H 2 , H 3 , n 1 , n 2 , n 3 are material constants while δ u and δ 1 are the indentation depths that separate regions, I, II and III respectively.…”
Section: Analysis Of Dislocations and Crystal Defects In The Ta Substsupporting
confidence: 91%
“…Guerrero et al [6] carried out MD simulation of uniaxial compression of nanocrystalline tantalum using their in-house developed EAM potential function to study the elastic-plastic transition on three crystallographic directions namely, (100), (110) and (111). They monitored the variation of phonon with respect to the applied strain rate and based on this, they concluded that the nucleation of defects along (110) of Ta was due to crystal twinning arising out of dynamical instabilities (soft phonons).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tantalum is often used for testing purposes, for study of yield strength, and for comparing theoretical predictions of elastic and plastic properties under extreme pressure and temperatures [41][42][43]50,[54][55][56]58,73,83,84,87,88]. As was mentioned above, tantalum possesses the BCC structure at ambient conditions and this structure remains stable up to at least 1.74 Mbar [42,43].…”
Section: Strength and Elasticity Of Nb And Tamentioning
confidence: 99%
“…Antonangeli et al [73] have presented a description of the elastic-plastic phase transitions in terms of an anomalous behavior of the elastic modulus under compression above 1 Mbar pressure. Guerrero and Marucho [84] have utilized classical molecular dynamics (MD) to study the elastic-plastic transition under uniaxial stress in defect-free BCC tantalum crystals. They demonstrated that the nucleation of the defects at the time scale of MD is due to dynamical instabilities (soft phonons) along the [100] direction.…”
Section: Strength and Elasticity Of Nb And Tamentioning
confidence: 99%